LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN FIQIH MATERI PUASA DI KELAS VIII MTS SULI - Muhaini Saputri; Makmur; St Marwiyah (JIP: Jurnal Ilmu Pendidikan, 2025)
Research objectives: 1) To find out the design of student worksheets on mandatory fasting and sunnah fasting material based on problem-based learning in class VIII MTs Suli. 2) To determine the validity of student worksheets on mandatory fasting and fasting sunnah based on Problem Based Learning in class VIII MTs Suli. 3) To determine the practicality of student worksheets on mandatory fasting and sunnah fasting material based on Problem Based Learning (PBL) in fiqh class VIII MTs Suli. 4) To determine the effectiveness of using student worksheets on mandatory fasting and problem-based sunnah fasting in improving learning outcomes in Class VIII MTs Suli. The type of research used is R&D (Research and Development) research. researchers use the ADDIE development model with five stages of development, namely the analysis, design, development, implementation and evaluation stages. This research was conducted at MTs Suli. The subjects in this study were class VIII students in the 2023/2024 school year. Data were obtained through product validation to media experts and material experts, practicality tests by Fiqh teachers, student response questionnaires by 27 MTs Suli students and pre-test and post-test questions. The data analysis technique used is descriptive qualitative and descriptive quantitative analysis. The results of this study are: 1) the results of the design of teaching materials are used to answer questions. 2) validity is declared feasible based on 80% media experts and 93% material experts. 3) the results of the practicality of the Fiqh teacher were declared very practical 91% and the student response questionnaire was very practical 94%. 4) teaching materials are declared effective based on the results of the pre-test and post-test questions (61.66 and 80.74).